2008
DOI: 10.1017/s1092852900013754
|View full text |Cite
|
Sign up to set email alerts
|

The Subgenual Anterior Cingulate Cortex in Mood Disorders

Abstract: INTRODUCTION-In the latest edition of our series of neuroanatomical areas of importance for neuropsychiatry, Wayne Drevets, MD, and Jonathan Savitz, PhD, have outlined the clinical importance of the ventral anterior cingulate structures for the regulation of mood. This area was an early target for interventional neurosurgery for depression some half a century ago, and today has become one of the key sites of deep brain stimulation for affective disorders. The anterior cingulate cortex was a part of the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
661
2
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 963 publications
(714 citation statements)
references
References 99 publications
(121 reference statements)
43
661
2
8
Order By: Relevance
“…Numerous studies using event-related and resting-state fMRI designs point to alterations in ACC activity in depressed patients (26)(27)(28)(29). The first resting-state fMRI study with MDD patients revealed a hyperconnectivity between the subgenual ACC and the DMN, confirming previous PET studies, which found resting state overactivity in ACC in these patients (30).…”
Section: Discussionsupporting
confidence: 70%
“…Numerous studies using event-related and resting-state fMRI designs point to alterations in ACC activity in depressed patients (26)(27)(28)(29). The first resting-state fMRI study with MDD patients revealed a hyperconnectivity between the subgenual ACC and the DMN, confirming previous PET studies, which found resting state overactivity in ACC in these patients (30).…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, OXT has been found to moderate ACC activity (Gorka et al, 2015;Scheele et al, 2014a), and the ACC is characterized by a high OXT receptor density (Boccia et al, 2013). More specifically, activation in this study was found in the subgenual ACC, which is especially involved in fear responses and shows abnormal activity in mood disorders (Drevets et al, 2008). Interestingly, this neural signature of the OXT IN effect was distinct from the conditioning-related cingulate cortex responses in the PLC group, which predominantly occurred in dorsal parts.…”
Section: Discussionmentioning
confidence: 47%
“…The current study indicates that already such a short and simple mindfulness instruction holds the potential of regulating emotion processing. The identified neural correlates of increased top-down prefrontal control over bottom-up emotion-generating processes are disrupted in psychiatric diseases such as depression (DeRubeis et al, 2008;Drevets et al, 2008). Thus, fostering mindfulness skills might hold the potential for strengthening emotion regulation and add support to the use of integrative approaches in psychotherapy that incorporate mindfulness practice (Segal et al, 2002;Hayes et al, 2004).…”
Section: Therapeutic Implications and Future Researchmentioning
confidence: 99%